Design and construction of micro fabrication cleanroom for teaching microelectronic undergraduate - Hashim, Uda; Zahid Jamal, Zul Azhar; Phang, K. C.; Nurzaihan, Mohamad; Abdul Halim, Nurhamidah; Abd Razak, Haffiz (Faculty of Electrical Engineering, 2006)

(untitled)
This paper describes about the experience of Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM) establishing the Micro Fabrication Cleanroom (MFC). This facility is mainly designed for teaching undergraduate microelectronic course leading to a Bachelorâ€™s degree. With the construction of its â€œMicro Fabrication Cleanroomâ€? (MFC), KUKUM has set the vision to reverse our reliance on imported technologies, as well as spearhead and support human resources needed by our nation, at the same time promoting indigenous talents and professionals especially in the field of microelectronic engineering. The cleanroom is approximately 115m2 with cleanliness class from ISO Class 5 in the Yellow Room to ISO Class 8 in the Grey Area (Utility Chase). The cleanroom are equipped with distributed process gases such as purified nitrogen, oxygen and compressed dry air and 18.0Mï?—ï€ ï€  ultra-pure water system supplied to the three fume hoods. Exhaust air from the fume hood are exhausted to the laboratory scrubber system for treatment. Despite being a teaching facility, the MFC cleanroom was designed and specified to ISO Class 5 cleanroom standard, and provided with features such as air shower, talk- through and pass box usually found in commercial facilities, it is our intention to expose and teach students to appreciate the stringent cleanroom protocols, in addition to the formal course works. This paper also describes the specifications, designs, development, testing, commissioning and operation of the cleanroom.